The nth term formula in an arithmetic sequence expresses any term based on its position in the sequence. It allows you to find the term at any given position \( n \) without needing to sequentially compute each prior term.
The general nth term formula for an arithmetic sequence is given by:
\[a_{n} = a_{1} + (n - 1)c\]
where:
- \( a_{n} \) is the nth term you're trying to find.
- \( a_{1} \) is the first term of the sequence.
- \( n \) is the position of the term.
- \( c \) is the common difference.
For our sequence \( 2, 5, 8, 11, 14, \ldots \), the first term \( a_{1} = 2 \) and common difference \( c = 3 \). Substituting these values, the formula becomes:
\[a_{n} = 2 + (n - 1) imes 3 = 3n - 1\]
This formula efficiently allows one to calculate any term directly, for instance, the 4th term is \( 3 \times 4 - 1 = 11 \).